Decision Algorithms for the Retreatment with Viscosupplementation in Patients Suffering from Knee Osteoarthritis: Recommendations from the EUROpean VIScosupplementation COnsensus Group (EUROVISCO). (July 2018) - Raman, Raghu; Henrotin, Yves; Chevalier, Xavier; Migliore, Alberto; Jerosch, Jörg; Montfort, Jordi; Bard, Hervé; Baron, Dominique; Richette, Pascal; Conrozier, Thierry
Background: Viscosupplementation (VS) is a symptomatic treatment of knee osteoarthritis. Although systematic reviews of its repeat use showed favorable benefit/risk ratio, no study has focused on the indication of retreatment. Methods: A task force was created to look at issues regarding retreatment with VS in knee osteoarthritis. An attempt was made to reach consensus on several issues: (1) to define treatment "success" and "failure, " (2) to determine when to retreat patients successfully treated by a previous VS, (3) to determine how to retreat patients in whom VS failed, (4) to define what to do in case of adverse reaction following previous VS, and (5) to examine the interests of soluble biomarkers to manage retreatment. After debate and review of literature the working group voted on 88 issues. Two "decision trees" were built based on the results of the votes. Results: In case of failure, the authors draw attention to the need of a rigorous clinical and radiological analysis, and consider evidence-based medicine. When VS was previously successful, retreatment can be considered after recurrence or increase in pain. However, in subjects with high risk of disease progression, in young patients, and in professional sportsmen, retreatment could be considered systematically, because of the probability of hyaluronic acid to slow osteoarthritis progression. Evidence on soluble biomarkers was not considered as enough strong to support their use as decision tools for patient retreatment. Conclusion: The decision algorithms are intended to facilitate consideration of the therapeutic options, in patients with knee osteoarthritis previously treated with VS.